Steeped in blood : adoption, identity, and the definition of family - Latchford, Frances J. (Frances Joan) (McGill-Queen's University Press, 2019)
"What personal truths reside in biological ties that are absent in adoptive ties? And why do we think adoptive and biological ties are essentially different when it comes to understanding who we are? At a time when interest in DNA and ancestry is exploding, Frances Latchford questions the idea that knowing one's bio-genealogy is integral to personal identity or a sense of family and belonging. Upending our established values and beliefs about what makes a family, Steeped in Blood examines the social and political devaluation of adoptive ties. It takes readers on an intellectual journey through accepted wisdom about adoption, twins, kinship, and incest, and challenges our naturalistic and individualistic assumptions about identity and the biological ties that bind us, sometimes violently, to our families. Latchford exposes how our desire for bio-genealogical knowledge, understood as it is by family and adoption experts, pathologizes adoptees by posing the biological tie as a necessary condition for normal identity formation. Rejecting the idea that a love of the self-same is fundamental to family bonds, her book is a reaction to the wounds families suffer whenever they dare to revel in their difference. A rejoinder to rhetoric that defines adoptees, adoptive kin, and their family intimacies as inferior and inauthentic, Steeped in Blood's view through the lens of critical adoption studies decentres our cultural obsession with the biological family imaginary and makes real the possibility of being family in the absence of blood."--